Assessment Of Third Ventricular Parameters in Computed Tomography of Head: A Pilot Study in Tertiary Level Hospital - Khanal, Umesh P; Sah, Keshav; Chand, Ram B (Journal of Institute of Medicine Nepal, 2020)
Introduction Measurement of ventricles of the brain is important for evaluating changes due to growth, ageing, intrinsic and extrinsic pathologies. The aim of this study was to determine the various parameters of the third ventricle and to assess their association with gender and age using computed tomography (CT) scans of head. Methods This retrospective, quantitative, cross sectional study was performed in the Department of Radiology and Imaging, Tribhuvan University Teaching Hospital from July to October 2019 (4 months) on images of 100 patients (50 males and 50 females) whose age group were 18-87 years, who underwent non-contrast and contrast enhanced CT scan of head. Results The total mean of width of third ventricle was found to be 0.33±0.09 cm, 0.35±0.10 cm in male and 0.31±0.06 cm in female. Third ventricle width (TVW) showed statistically significant correlation with male and also with Age. Mean of third ventricle sylvian fissure distance index was 0.41±0.67 cm, 0.42±0.65 cm in male and 0.39±0.06 cm in female respectively. Mean of third ventricle ratio was 0.03±0.09 cm, 0.03±0.09 cm in male and 0.02±0.09 in female respectively. The value were slightly higher in male. Conclusion The third ventricle width in CT in this study was 0.33±0.09 cm. CT was very useful to determine the upper limits of normal value and its variation with age.